Association of single nucleotide polymorphism in leptin gene with growth traits of Jamunapari goat - DIGE, MAHESH SHIVANANAD; KAUSHIK, RAKESH; MISHRA, CHINMOY; VERMA, MAHIMA; PAWAIYA, RVS; BHUSAN, SAKET; ROUT, PRAMOD KUMAR (The Indian Journal of Animal Sciences, 2021)
The current study sought to identify single nucleotide polymorphisms (SNPs) in the leptin gene and investigate their relationship with growth traits in goats. Phenotypic data for birth weight (BW), weaning weight (WW), body weight at six month (6MW), body weight at nine month (9MW) and body weight at twelve month (12MW) from Jamunapari goats were recorded. Seven pairs of primers were designed to amplify the leptin gene spanning promoter, exonic, intronic and 3’ UTR regions by polymerase chain reaction. High Resolution Melting (HRM) was employed for genotyping, and DNA sequencing was utilized to mining SNPs. Four novel SNPs at g.584C>T, g.4226T>C, g.4158T>C and g.4133T>A were identified in promoter region and 3' UTR region of leptin gene. Statistical analysis revealed that SNPs at g.584C>T was associated with weaning and post weaning stages of growth. Moreover, goats with the CT genotype had higher body weight at WW, 6MW, 9MW and 12MW than those with CC genotype. The results of this study demonstrated that SNPs in leptin gene was significantly associated with growth traits in goat. These findings suggest that an SNP in the caprine leptin gene could be one of the candidates for improving body weight in the Jamunapari goat.